Natural and Man-Induced Hazards Along the Danube, between Rast and Gighera Settlements, with a Special View on the 2006 Flood - Licurici, Mihaela; Boengiu, Sandu; Ionuş, Oana (Quaestiones Geographicae, 2011)
he paper discusses the natural and man-induced hazards in the Rast-Gighera sector of the Danube Floodplain, an area displaying asymmetric character, with the high and steep slopes of the Prebalcanic Tableland dominating the low Romanian ﬂoodplain. The subject regards an acute present problem, the necessity to impro-ve the management of dangerous phenomena included among the objectives for this millennium. Moreover, the paper regards a space with an exceptional natural heritage that has been seriously transformed by man, the natural-human opposition becoming the key-element of the region. The complexity of the subject is given by the plurality of causes that lead to the genesis of hazards. Their nature, frequency and intensity, along with other factors of psychological or economic nature imply different answers from the part of the affected population. In the past, the region was characterised by the significant presence of swampy areas, lakes and ponds connected to the Danube through secondary branches, being under the influence of the level oscillations of the river. The relief was strongly modified, especially during the last hundred years, the human factor exerting an important influence, mainly through flood-control dykes and dams, networks of irrigation and drainage channels, deforestation, so that extended surfaces that had been naturally covered by waters and forests were converted to agriculture.